Entrepreneurship and Community between Embeddedness and Affective Economy: ethnography of an Alpine dairy production - Michele Filippo Fontefrancesco (Narrare i Gruppi, 2024)
The article explores the relationship between enterprise and territory, delving into and applying the concepts of embeddedness and affective economy to ethnographic analysis. In doing so, it examines and deepens the case study of the Italian alpine village of San Lazzaro and its Formatge , a local product for which the community is known and characterized as a tourist destination. The analysis of food stories collected among the various actors of the community focusing on this product highlights not only the deep integration between company knowledge and ideals and community horizons but also demonstrates how companies and products cannot be understood outside the community context in which they are produced and contribute to building.